Assessment of Crude Oil Degradation by Mixed Culture of Bacillus subtilis and Pseudomonas aeruginosa at Different Concentrations - Faggo, A.A.; Kawo, A.H.; Gulumbe, B.H.; Ijah, U.J.J. (International Journal of Environment, 2020)
Petroleum hydrocarbon (PHCs) contamination of soil, freshwater and air is of global concern. The aim of this study was to assess the extent of crude oil degradation by mixed bacterial culture of different crude oil concentrations using gas chromatography-mass spectrometry (GC-MS). Seven oil samples were collected from petroleum-contaminated fields in Kano state, Nigeria, and screened for crude oil utilizing bacteria. A control sample of soil from an ecological garden (control soil) was also analyzed. Crude oil-degrading bacteria were isolated, enumerated and identified using cultural, morphological and biochemical characteristics, and screened for their ability to utilize Bonny Light Oil as a source of carbon and energy. Bacteria with the highest potential to utilize crude oil were selected and subjected to bioremediation studies at three different pollution levels (5%, 10% and 15%) for 56 days. The residual crude oil was assessed using GC-MS. The results revealed that the mixed culture completely degraded eighteen components ranging from C10 to C25 at 5% crude oil concentration while only C8 to C11 and C8 to C9 were degraded at 10 and 15% respectively. The results of this study indicated the potential of B. subtilis and P. aeruginosa in bioremediation of crude oil contaminated soil.